The spy who loved me - Fleming, Ian 1908-1964 ([Burbank, Calif. Warner Home Video, 1977)
Agent 007 joins forces with a beautiful Russian agent to battle a mad genius, multi-millionaire shipping magnate Karl Stromberg. Stromberg plans to destroy the earth and rebuild it underwater, and is in possession of an ultra- sensitive submarine tracking system which he seems to be offering to the highest bidder. After he captures a British submarine, Bond's job is to recover the tracking device and free the submarine.
Made by EM Productions.
Based on a novel by Ian Flemming.
Videotape released of the 1977 motion picture.
VHS.
Screenplay by Christopher Wood and Richard Maibaum ; produced by Albert R. Broccoli ; directed by Lewis Gilbert.
Roger Moore, Barbara Bach, Curt Jurgens, Richard Kiel.
Keywords: Bond, James (Fictitious characters) -- Drama; Spy stories, English -- Film and video adaptations; Feature films; Spy films